Descubriendo la naturaleza para protegerla mejor - Un proyecto de aprendizaje por Metodología de Proyectos - Tavares Pitau, Joana (2024)
This article reflects the learning process carried out within the framework of an environmental education and educational intervention project, using the Project Work Methodology (MTP), conducted in the context of preschool education in Portugal. Following a qualitative paradigm, the study aims to analyze how children develop skills through the MTP. The approach respected children’s individual needs, fostering critical and creative thinking. The educational intentions constructed during the intervention led to the promotion of different types of learning among the children. The recorded evidence reveals benefits in their holistic development, confirming the formative potential of the project methodology.